2002
DOI: 10.1159/000064119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lesions of Nucleus taeniae on Appetitive and Consummatory Aspects of Male Sexual Behavior in Japanese Quail

Abstract: Neurochemical, hodological and functional criteria suggest that the nucleus taeniae and parts of the adjacent archistriatum represent the avian homologue of parts of the mammalian amygdaloid complex. It has been proposed in particular that the nucleus taeniae is the homologue of the mammalian medial amygdala. In male quail, relatively large lesions to the posterior/medial archistriatum selectively decrease the expression of appetitive sexual behavior in a manner reminiscent of similar manipulations involving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 56 publications
6
73
1
Order By: Relevance
“…This increased expression of SRC-1 in ASSC birds is likely to have caused the major increase in behavioral frequencies because no changes in plasma testosterone were expected to occur during this short period (SILASTIC capsules release testosterone at a constant rate; see Materials and Methods). Previous work also indicates that, once castrated male quail treated with SILASTIC implants filled with testosterone have reached their maximal sexual activity, the frequencies of behaviors they express during repeated testing (up to 10 tests) remain stable for extended periods of at least 1 or 2 weeks (Balthazart et al, 1988Dermon et al, 1999;Tlemçani et al, 2000;Absil et al, 2002b). Spontaneous changes in behavioral frequency of the magnitude detected here (doubling or more) were never observed in any of these studies.…”
Section: Methodssupporting
confidence: 61%
“…This increased expression of SRC-1 in ASSC birds is likely to have caused the major increase in behavioral frequencies because no changes in plasma testosterone were expected to occur during this short period (SILASTIC capsules release testosterone at a constant rate; see Materials and Methods). Previous work also indicates that, once castrated male quail treated with SILASTIC implants filled with testosterone have reached their maximal sexual activity, the frequencies of behaviors they express during repeated testing (up to 10 tests) remain stable for extended periods of at least 1 or 2 weeks (Balthazart et al, 1988Dermon et al, 1999;Tlemçani et al, 2000;Absil et al, 2002b). Spontaneous changes in behavioral frequency of the magnitude detected here (doubling or more) were never observed in any of these studies.…”
Section: Methodssupporting
confidence: 61%
“…The Forum also concluded that hodological, developmental, neurochemical, and behavioral evidence supported the amygdaloid nature of the taenia and posterior archistriatum (Zeier and Karten, 1971;Veenman et al, 1995b;Lanuza et al, 2000;Puelles et al, 2000;Absil et al, 2002;Roberts et al, 2002). By contrast, the anterior, intermediate, and at least parts of the medial archistriatum have largely somatic features, making them unlike the amygdala in mammals (Zeier and Karten, 1971;Veenman et al, 1995b;Davies et al, 1997;Mello et al, 1998b;Reiner et al, 2002;Wada et al, 2001).…”
Section: Rationale For Individual Changes: the Archistriatummentioning
confidence: 97%
“…Based on neurochemical and developmental data, it seemed overwhelmingly clear to the Forum that all parts of the archistriatum (i.e., the regions with the word archistriatum in their name) as defined in Karten and Hodos (1967) and in Kuenzel and Masson (1988) are pallial Wada et al, 2001, Reiner et al, 2002Sun et al, 2003). The Forum further concluded that the taenia (also called the nucleus taeniae) has typically been regarded as a part of the archistriatal complex, although this was not reflected in its name (Ariëns-Kappers et al, 1936;Zeier and Karten, 1971;Thompson et al, 1998;Chen et al, 1999;Absil et al, 2002) and that much or all of the taenia is subpallial (Foidart et al, 1999;Cobos et al, 2001b;Absil et al, 2002).…”
Section: Rationale For Individual Changes: the Archistriatummentioning
confidence: 99%
See 1 more Smart Citation
“…In quail, steroid-sensitive areas such as the medial part of the bed nucleus striae terminalis and parts of the arcopallium including the nucleus taeniae of the amygdala are also clearly involved as indicated by a number of studies based on targeted electrolytic lesions and on the analysis of c-fos expression [2,29,49,137,140]. This is also clearly the case and documented in more detail in other species such as rodents in which areas such as the parts of the amygdala play a critical role in the integration of chemosensory and hormonal cues mediating mating behavior [99,154,155].…”
Section: Anatomical Studiesmentioning
confidence: 99%